PERBEDAAN KETERAMPILAN KLINIS PEMERIKSAAN LEOPOLD PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2016 YANG DIFASILITASI OLEH INSTRUKTUR DENGAN MAHASISWA SENIOR TERLATIH - IDA NUYANI; MEIZLY ANDINA (LP2MTBM MAKARIOZ, 2020)
Peer Assisted Learning (PAL) is a student-centered learning method with peers or called peer tutors as instructors and tutee(students) as taught by peer tutors. The process of learning with peers or what is known as the term PAL has long been usedas a learning method in medical science. This approach with the PAL technique allows friends or seniors to help their friendsor juniors in the learning process and provide support to improve clinical skills while studying in the medical world. To find outthe difference in clinical skills of Leopold examination in 2016 students of the Medical Faculty of the University of NorthSumatra Muhammadiyah who were facilitated by instructors with trained senior students. This type of research isquantitative, with the research design used is true experimental with post test only control design. Based on the Mann-Whitney Test results obtained a p value of 0.976 (p> 0.05), statistically showed that there was no significant differencebetween the clinical skills of the Leopold examination facilitated by instructors and trained senior students. There was nodifference between Leopold clinical examination skills facilitated by instructors and trained senior students.